Kinetic and physicochemical characterization of strawberry fermented (Research, Society and Development, 2021)
Strawberry is a demanding crop in relation to temperature and climatic conditions, its cultivation in a protected environment, produces fruits rich in sugars such as sucrose, fructose and vitamins, it also has few carbohydrates, making it very tasty accepted by consumers. Its commercialization can also be as jelly and pulp, juices and fermented. The preparation of the fermented strawberry is not a drink that is widely commercialized in Brazil, despite the knowledge about its production. Thus, the present work aims to analyze the kinetics and the physicochemical characterization of strawberry fermented in protected cultivation with three strawberry cultivars in the Campos Gerais Region. The design was completely randomized with 4 repetitions each. Three treatments: control, a treatment with the yeast Saccharomyces cerevisae and Saccharomyces bayanus. For chemical analysis, the content of soluble solids was performed with a digital refractometer. Titratable acidity (% citric acid) and pH were also analyzed, as well as phenolic variables and kinetic profile. Soluble solids was not significant, for phenolic variables, Saccharomyces bayanus presented the highest levels when compared to other treatments, as well as it took longer to form the production in the kinetic profile. Some authors report that organic acids present in fruits interfere with the activity of the strain.